The language policy and the institutional practices of the language interaction - Ikilikyan, Sona G.; Karapetyan, Elena A.; Kanevski, Ashot A.; Viktoria V. Posidelova5Roman A. Pestov (Opción, 2020)
The article analyses the peculiarities of the language policy and the institutional practices of language interaction in the Russian multinational society via comparative qualitative research methods. As a result, here is a lack of definitely written traditions, the demanded terminologies, and such other things are not enough elaborated in many republics. In conclusion, the language policy of the Russian Federation, on the whole, creates favorable conditions for the formation, maintenance and strengthening of national identities in the Russian society.